Racial microaggressions within social work: perceptions of providers. Issue 1 (2nd January 2020) - Weng, Suzie S.; Gray, Lisa
ABSTRACT: This article examines racial microaggressions within social work practice from the perceptions of providers. Semi-structured qualitative interviews were conducted with 30 social workers about racial microaggressions and strategies for combating them in social work practice. Themes emerged include: (1) identifying racial microaggressions in social work settings; (2) proposing strategies for addressing racial microaggressions; and (3) identifying and responding to racial microaggressions in the institutional environment. The implications drawn from the study's findings, highlight areas for consideration within social work practice that may help to guide subsequent efforts towards recognising, minimising, and responding to racial microaggressions within social work.